Luminescent polyoxotungstoeuropate anion-pillared layered double hydroxides - Sousa, Filipa L. (2006)
Novel luminescent polyoxometalate anion-pillared layered double hydroxides (LDHs) were prepared by aqueous ion exchange of a Zn–Al LDH precursor in nitrate form with the europium-containing polyoxotungstate anions [EuW10O36]9–, [Eu(BW11O39)(H2O)3]6– and [Eu(PW11O39)2]11–. The host– guest interaction has a strong influence on the nature of the final intercalated species, as evidenced by elemental analy- Introduction Layered double hydroxides are an important class of ionic lamellar solids with the general formula [M2+ 1–xM3+ x(OH)2](Am–)x/m·nH2O (M2+ = Mg2+, Zn2+, Ni2+ etc., M3+ = Al3+, Cr3+, Ga3+ etc).[1] The positively charged layers, containing divalent and trivalent cations in octahedral positions, are separated by charge balancing anions and water molecules. The water molecules are connected to both the metal hydroxide layers and the interlayer anions through extensive hydrogen bonding. A range of organic or inorganic guests may be incorporated into LDHs by either ion exchange, direct synthesis or hydrothermal reconstruction of calcined precursors.[2,3] In particular, intercalation chemistry has been explored with the aim of introducing catalytically active sites and photo- and electroactive species. Many different types of metal coordination compounds and oxometalates have been immobilized in LDHs, including phthalocyanines, cyanocomplexes, oxalate complexes and polyoxometalates (POMs).[4] The first report of LDHs containing polyoxometalates concerned their use as exhaust gas and hydrocarbon conversion catalysts.[5] Since then, a variety of iso- and heteropolyanions with different nuclearities and structures (Keggin, Dawson, Preyssler, Finke) have been incorporated into the interlayer space of these materials.[6–18] Two factors assume considerable importance for the successful intercalation of polyoxometalates into an LDH compound. First, the heteropoly species should carry sufficient charge in order to be [a] Department of Chemistry, CICECO, University of Aveiro, 3810-193 Aveiro, Portugal E-mail: helena@dq.ua.pt [b] Department of Physics, CICECO, University of Aveiro, 3810-193 Aveiro, Portugal © 2006 Wiley-VCH Verlag 726 GmbH & Co. KGaA, Weinheim Eur. J. Inorg. Chem. 2006, 726–734 sis, powder X-ray diffraction (XRD), infra-red (IR) and Raman spectroscopy, solid state magic-angle spinning (MAS) 11B and 31P NMR spectroscopy, and photoluminescence spectroscopy.